The Tendency of Breaking Arranged Marriages in Indian Subcontinent and Ways of Peaceful Co-Existence in the light of Islam - Rahman, Md Masudur (IIUC Studies, 2012)
Breaking arranged marriage has become of late a common phenomenon in the Muslim society of the Indian sub continent. For this, misunderstanding, clash and quarrels break out inside the family and society. Family loses money, peace and tranquility. This is disgusting burden for the society and obstacles to development also. This article discusses the reasons of breaking arranged marriages and has given a suggestion to reduce the tendency of misunderstanding of the conjugal life in the light of the religion of Islam. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12269 IIUC Studies Vol.7 2011: 221-240